Saber direito: leituras e escritas a partir do ECA no ensino fundamental II - Giuliano César dos Santos (2020)
By living in society, man tends to deal with conflicts, disagreements, which, as a rule, should be discussed and remedied by law, which is hampered by the inaccessibility circumstance imposed on a good part of the population, in what concerns knowledge and participation in laws. Despite the existence of moralistic discourses associated with young people in contemporary times and recent discussions about reducing the age of criminal responsibility, this legal discourse is still a long way from this audience, especially from the poor teenager, very associated with criminality, mainly by sectors of investigative journalism. Supported in a Bakhtinian perspective regarding language as an interactional process, in which speakers and listeners are considered in their condition as subjects, this research, of a qualitative-interpretative character, was developed in a public elementary school II, where students of 9th year answered two questionnaires, which were presented to them before and after a teaching project developed in 20 classes, through 3 stages. The first refers to reflections on the condition of the subject as a young person, the second seeks to bring the student closer to the law genre and the third, more directly linked to the production of texts. Applying the indisciplinary perspective of LA (MOITA LOPES, 1996), and of Freire's conceptions (1979 and 1996), we approach language teaching through a critical posture in relation to the environment, to the society in which it is produced, which includes approximation, understanding of the laws by the student. Thus, using the Child and Adolescent Statute (ECA) as an instrument and through a concept of socio-historical language, we aim to identify previous knowledge and also analyze the readings and the production of texts linked to the legal theme. Such production was published in the form of memes on Instagram. This research resulted in the importance of reframing about what may be youth, a critical stance towards legality and also the confirmation that the production of texts aimed at a real discursive context contributes to a greater engagement of the student.